Effect of storage temperature on the flavour of citrus fruit - Marcilla, Alicia; Zarzo, Manuel; Del-Río, Miguel A. (2017)
This paper reports the effect of different storage temperatures (5, 15, 20 and 25 degrees C) on the flavour of cv. Valencia Late Frost oranges stored for up to one month (following a pre-experimental two month storage period at 5 degrees C). Samples were instrumentally analysed every week for titratable acidity, soluble solid content, maturity index, and ethanol and acetaldehyde contents. In addition, four sensory attributes were assessed by 20 taste panellists (this work formed part of their training): acidity, maturity index, off-flavours and orange-like flavour. Principal components analysis was performed to determine the correlation structure of the sensorial data. This showed that the presence of off-flavours reduced the orange-like flavour perceived, but affected neither the acidity nor the maturity index. Acidity correlated negatively with the sensorially-perceived maturity index. The higher temperatures reduced the orange-like flavour and increased the presence of off-flavours over storage; this had a negative impact on the sensorial quality of the fruit. These effects were statistically significant, though more accurate results may have been obtained had the panellists received more training.